Subduction transference drove the Mesozoic convergence of microcontinents from Gondwana to Asia - Yiming Ma; Mark J. Dekkers; João C. Duarte; Timothy Kusky (Communications Earth & Environment)
Abstract How microcontinents successively migrated from Gondwana to Eurasia is paramount in understanding the Mesozoic evolution of the Tethys Ocean. The rifting and collision events and their potential spatio-temporal relationship may play a key role in this evolution. We compiled available Permian-Jurassic paleomagnetic data from the Lhasa terrane, revealing that it drifted away from Gondwana ~210 million years ago, which is ~10 million years earlier than the South-North Qiangtang collision. Similarly, the Lhasa-Qiangtang collision preceded the rifting of India by ~10 million years. These age gaps of similar kinematic circuits align well with the time required for collision-induced subduction transference, whereby a new subduction zone forms outboard of the newly accreted terrane. Then, the slab-pull force can be transmitted to the southern segment of the younger Tethys slab by coupling across the oceanic ridge/transform system, such that subduction transference drives the in-sequence one-way convergence of microcontinents with Eurasia.